Pola Pertumbuhan Kerang Mangrove Geloina erosa Kawasan Ekosistem Mangrove Pesisir Barat Kabupaten Aceh Besar - M. Ali Sarong (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2009)
Geloina erosa as one of Bivalve species has growth and development comprising the proliferation of the shell length, volume, and body weight. Generally, the growth of G. erosa has negative allometric, isometric and  positive allometric fashion. This encourages the study of G. erosa living in the region of mangrove ecosystem of west-coast of Aceh Besar. The objectives of the research are to determine the growth pattern of shell length against body weight as well as the growth pattern of shell length against its total body weight. The research was conducted from February 2006 to January 2007 in the region of mangrove ecosystem of west-coast of Aceh Besar. The region was divided into three different locations. Each location was set a sample square with 10m x 10m in size which was perpendicular to coastal lines. There were 10 sub-squares also set in every sample square with 50cm x 50cm in size. Sample collection in the sub-square was carried out by scratching and disturbing the bottom of the waters in order to sieve them. G. erosa was then measured for its shell length, body weight, and total body weight. The growth pattern was analyzed by using Excel program and t-test. The result showed that a negative allometric growth pattern was found in the measurement of shell length against total body weight of G. erosa, whereas an isometric pattern was found of the measurement of shell length against its body weight. Moreover, a positive allometric pattern was figured out in the measurement of shell length against total body weight. The proliferation of shell length, body weight and total body weight has contributed approximately 58% to 59%. This indicates that the growth pattern of G. erosa in the region of mangrove ecosystem of west-coast of Aceh Besar has negative allometric, isometric and positive allometric fashion.